PENERAPAN ANALISIS KELOMPOK MENGGUNAKAN KRITERIA INFORMASI AKAIKE’S SEBAGAI UJI BANDING MODEL PEMBELAJARAN COOPERATIF LEARNING - Elfitra Elfitra (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2015)
Application of cluster analysis using Akaike's information criterion as a comparative test model cooperative learning. Ussualy in procces of comparing sample of many observation, many method are used. The purpose of some of thes methods is to test the similarity hypothesis pair, but difficult to filter the specific properties of data. An alternative procedure introduced by not involving test of hypothesis. Cluster analysis method introduced here using the algorithm introduced models Akaikes Information Criterion (AIC) to see a pair of groups that have similarities. Research result is cooperative learning type Jigwas and STAD (Student Teams Achievement Divisions) have similarity. Both of model has a differences with Numhead Together (NHT) model’s.